Microwave-Assisted Claisen-Schmidt Condensation Reaction of Ethyl p-methoxycinnamate to Synthesize p-Methoxystyryl Ketone Derivatives and Evaluate Anti-inflammatory Activity of Synthetic Products - Ismiarni Komala; Supandi Supandi; Nurmeilis Nurmeilis; Yardi Yardi; Ofa Suzanti Betha; Nurkhyati Putri Indriyani; Moethia Moethia; Muhamad Beny Setiawan; Ghilman Dharmawan; Putri Hayati Nufus; Noni Tri Utami (Journal of Mathematical and Fundamental Sciences, 2021)
The rhizome of Kaempferia galanga has been known to contain ethyl p-methoxycinnamate (EPMC) (1) as a main component, which has anti-inflammatory properties. Previously we have reported the structural modification of EPMC (1) to form another ester, nitrostyrene, and cinnammamide derivatives and then studied their structure-activity relationships as anti-inflammatory agent. In continuing our research, in this paper, we report the microwave-assisted Claisen-Schmidt condensation of EPMC (1) to synthesize a series of p-methoxystyryl ketones followed by a study of their anti-inflammatory activity. The reaction begins with microwave-assisted cleavage oxidation of hydrolyzed product of EPMC, p-methoxycinnamic acid (2) with Ca(NO3)2 for the synthesis of p-methoxybenzaldehyde (3). Furthermore, 3 was reacted with acetophenone, ethyl methyl ketone and acetone via microwave-assisted Claisen-Schmidt condensation for the synthesis of (E)-1-(4-methoxyphenyl)-3-phenylprop-2-en-1-one (5a) (E)-1-(4-methoxyphenyl)pent-1-en-3-one (5b) and (E)-4-(4-methoxyphenyl)but-3-en-2-one (5c), respectively. The reaction products were characterized using spectroscopic techniques and were then tested for anti-inflammatory activity using in vitro anti-denaturation of protein assay. It was found that converting EPMC (1) to 5a and 5b reduced anti-inflammatory activity, while 5c retained anti-denaturation activity with an IC50 of 72.8 µg/ml.